Neuronal activity and remyelination: new insights into the molecular mechanisms and therapeutic advancements - Zhou, Yiting; Zhang, Jing (Frontiers in Cell and Developmental Biology, 2023)
This article reviews the role of neuronal activity in myelin regeneration and the related neural signaling pathways. The article points out that neuronal activity can stimulate the formation and regeneration of myelin, significantly improve its conduction speed and neural signal processing ability, maintain axonal integrity, and support axonal nutrition. However, myelin damage is common in various clinical diseases such as multiple sclerosis, stroke, dementia, and schizophrenia. Although myelin regeneration exists in these diseases, it is often incomplete and cannot promote functional recovery. Therefore, seeking other ways to improve myelin regeneration in clinical trials in recent years is of great significance. Research has shown that controlling neuronal excitability may become a new intervention method for the clinical treatment of demyelinating diseases. The article discusses the latest research progress of neuronal activity on myelin regeneration, including direct or indirect stimulation methods, and the related neural signaling pathways, including glutamatergic, GABAergic, cholinergic, histaminergic, purinergic and voltage-gated ion channel signaling pathways, revealing that seeking treatment strategies to promote myelin regeneration through precise regulation of neuronal activity has broad prospects.